2013
DOI: 10.3354/aei00066
|View full text |Cite
|
Sign up to set email alerts
|

Influence of climate on Pelorus Sound mussel aquaculture yields: predictive models and underlying mechanisms

Abstract: Multiple regression models were used to predict aquaculture production in Pelorus Sound, a 50 km long estuary supporting 68% of New Zealand's greenshell mussel Perna canaliculus aquaculture industry (worth NZ$ 204 million per annum). Mussel meat yield was modelled using both biological predictors, including seston (indexed by particulate nitrogen, PN), phytoplankton and nutrients collected over 9 yr (July 1997 to November 2005 by the mussel industry, and physical, climatic predictors, including Southern Oscill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 45 publications
4
29
1
Order By: Relevance
“…The drag coefficient was therefore multiplied by a factor that was adjusted to optimise agreement: the final value chosen was 1.2. A similar adjustment has been found to be necessary for previous coastal modelling exercises around New Zealand (Hadfield and Zeldis 2012;Zeldis et al 2013). The need for this adjustment may indicate that the NZLAM wind speeds are biased low and/or that the Smith (1988) drag coefficient formula gives results that are too low for the wind and wave conditions in coastal areas.…”
Section: Model Setup and Forcingmentioning
confidence: 80%
See 1 more Smart Citation
“…The drag coefficient was therefore multiplied by a factor that was adjusted to optimise agreement: the final value chosen was 1.2. A similar adjustment has been found to be necessary for previous coastal modelling exercises around New Zealand (Hadfield and Zeldis 2012;Zeldis et al 2013). The need for this adjustment may indicate that the NZLAM wind speeds are biased low and/or that the Smith (1988) drag coefficient formula gives results that are too low for the wind and wave conditions in coastal areas.…”
Section: Model Setup and Forcingmentioning
confidence: 80%
“…Oceanographically, it is perhaps best known for its strong tidal currents (Vennell 1998) and the consequent high levels of turbulence (Stevens 2018). However, regionally at least, the subtidal fluxes of heat, salt and nutrients are of significant importance to natural and built ecosystems (Zeldis et al 2013;Chiswell et al 2017). Here we describe hydrodynamic model estimates of the volume flux through the Strait.…”
Section: Introductionmentioning
confidence: 99%
“…The freshwater flux from the Pelorus River generates relatively strong stratification after large rainfall events (Heath 1976b;Proctor and Hadfield 1998;Stevens and Smith 2016). Recently Stevens (2014) suggested that the oceanic source waters for the sounds might at times come from the east rather than from the west (Zeldis et al 2013). Long-term transport in the Sounds is primarily controlled by stratification (Sutton and Hadfield 1997).…”
Section: Marlborough Soundsmentioning
confidence: 99%
“…phytoplankton and other seston) to cultured Perna. In Pelorus Sound, temporal changes in Perna yield have been linked to changes in seston availability determined by oceanic upwelling at the entrance to the Sound and riverine nutrient inputs at the head (Zeldis et al 2008(Zeldis et al , 2013. Depending on location, farm-scale seston depletion may also occur (Keeley et al 2009, Stenton-Dozey 2013, with the extent depending on factors relating to environmental drivers, bay-scale farming intensity and farm-scale management (e.g.…”
Section: Perna Crop Yield and Impact Of Mytilusmentioning
confidence: 99%